Formation of pedagogical competencies in the field of physical culture and sports at the master’s degree courses of the Belarusian State University - Maslovskaya, Yuliya I. (University Pedagogical Journal, 2023)
The motives for studying at the master’s degree courses of the Belarusian State University are being considered, taking into account the profiling «Educational technologies in physical culture and sports». The main task in education of students of the second stage of higher education is the formation of universal pedagogical competencies based on the indepth professional knowledge.